Spatial Analysis of Rehabilitation Efforts for the Labor-intensive National Economic Recovery Program for Mangrove Planting (Case Study in the Coastal District of Ngombol, Purworejo) - Dian Rachmawati; Muhammad Kamal; Nurul Khakim (JPG (Jurnal Pendidikan Geografi), 2023)
Purworejo Regency has a narrow mangrove area along the Slope 2 River to the mouth of the Jali River with a wide area 100.22 ha, and 64.24 ha are in Ngombol District. This mangrove habitat is under pressure and degraded due to the development of shrimp farming and agricultural land. Many attempts to plant mangroves have been made but have always failed. In 2020 mangrove rehabilitation will be carried out through the National Mangrove Labor Intensive PEN program covering an area of 18,709 ha. One of the Mangrove Work-Intensive PEN activities was carried out in Ngombol District, namely in Wero Village, Pagak Village and Malang Village covering an area of 48 ha. However, the planting activity also failed. This study aims to (1) map the distribution of mangroves on the coast of Ngombol District; (2) carry out a spatial analysis of Mangrove Labor-Intensive PEN locations based on their land use, and identify the factors that cause failure of mangrove rehabilitation. Mapping of mangroves and land use was carried out through visual interpretation of Pleiades PMS satellite imagery with a spatial resolution of 0.5 m recorded on 30 July 2020. Sampling was carried out by purposive sampling. Spatial analysis was carried out through overlapping maps of rehabilitation locations and land use maps. The results of the study obtained a mangrove map with a scale of 1:10,000 with a mangrove distribution area of 40.13 ha.The results of the spatial analysis on the Mangrove Planting Labor-Intensive PEN rehabilitation location against the Land Use Map found that the planting location was located in mangrove land use (21.57 ha), former ponds (0.94 ha), vacant land (0.43 ha), grass / bush (12.73 ha), rainfed rice fields (2.71 ha) and rivers (9.63 ha). Several factors contributed to the failure of rehabilitation, including: the very short time for implementing rehabilitation activities, resulting in a lack of planning; plant type incompatibility; disrupted tidal cycle due to sediment in the estuary; flooding of the area around the river due to silting of the river; annual large inundation floods and community understanding that is still weak on the importance of mangroves and a lack of coordination between sectors. The results of this study serve as input for rehabilitation activity organizers so that future rehabilitation activities can be more targeted and successful.